40Ar-39Ar age of the copper mineralization at riacho do pontal IOCG district and detrital zircon U–Pb ages of paragneiss host rocks. (January 2023) - Bacelar Hühn, Sérgio Roberto; Silva, Adalene Moreira; Braitenberg, Carla; Rossignol, Camille; Avila, Janaina
Abstract: Geological, structural and metallogenetic characteristics related to the Proterozoic Riacho do Pontal iron-oxide copper gold (IOCG) mineral systems in northeast Brazil have been reinterpreted recently and there is an ongoing discussion regarding their genetic model and associated tectonic setting. The mineralization in the Riacho do Pontal district is represented by small copper deposits strongly controlled by the structural features of the basement rocks. Hydrothermal biotite associated with the copper mineralization has a 40 Ar- 39 Ar of ca. 691 Ma, indicating a probable late Neoproterozoic age for the main mineralization event. Detrital zircon grains from the host rock show that the sedimentary protolith is younger than ca. 2035 Ma and was probably deposited in a convergent setting. Our results help to understand the emplacement of this deposit in the tectonic context of the Riacho do Pontal Belt. Graphical abstract: Image 1 Highlights: Riacho do Pontal Belt comprises iron-oxide copper gold mineral systems. Copper mineralization occurred during the late Neoproterozoic. Sedimentary protolith is younger than ca. 2035 Ma. The main Cu mineralization event occurred at ca. 691 Ma.